1992
DOI: 10.1007/bf00180205
|View full text |Cite
|
Sign up to set email alerts
|

The suppression of heterotopic ossification after total hip arthroplasty

Abstract: In a double-blind prospective randomised study we examined the effects of Diclofenac on heterotopic ossification after hip arthroplasty. Either the drug, or a placebo, was given by mouth to 158 patients in doses of 3 x 50 mg for 6 weeks. Diclofenac resulted in highly significant improvement (p less than 0.0001 versus controls) without severe side-effects. Heterotopic ossification decreased from 55% in the placebo to 15%. Significant degrees of heterotopic ossification did not occur with the drug. Movement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…The incidence of heterotopic bone formation was high in our placebo group ( 15/22 patients). However, comparable studies, including a placebo group where no treatment with antiinflammatory drugs for 2-12 postoperative weeks had been given, show the same high incidence of the lesion (Elmstedt et al 1985, Schmidt et al 1988, Hoikka et al 1990, Gebuhr et al 1991, Wahlstrom et al 1991, Reis et al 1992, Kjaersgaard-Andersen et al 1993). Therefore, the true incidence of heterotopic ossification after total hip arthroplasty can only be determined in patients receiving postoperative treatment without antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The incidence of heterotopic bone formation was high in our placebo group ( 15/22 patients). However, comparable studies, including a placebo group where no treatment with antiinflammatory drugs for 2-12 postoperative weeks had been given, show the same high incidence of the lesion (Elmstedt et al 1985, Schmidt et al 1988, Hoikka et al 1990, Gebuhr et al 1991, Wahlstrom et al 1991, Reis et al 1992, Kjaersgaard-Andersen et al 1993). Therefore, the true incidence of heterotopic ossification after total hip arthroplasty can only be determined in patients receiving postoperative treatment without antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 95%
“…Randomized, double-blind and placebo-controlled clinical trials have shown that antiinflammatory drugs can prevent the severest degree of heterotopic bone formation after total hip arthroplasty when administered during the first 3-12 postoperative weeks (Elmstedt et al 1985, Schmidt et al 1988, Hoikka et al 1990, Gebuhr et al 1991, Wahlstrom et al 1991, Reis et al 1992, Kjaersgaard-Andersen et al 1993. We investigated in a randomized, double-blind and placebo-controlled clinical trial whether prophylaxis with indomethacin during only the first 2 postoperative weeks prevents the severest degrees of heterotopic bone formation after hip arthroplasty.…”
Section: Lndomethacin For Prevention Of Heterotopic Ossificationmentioning
confidence: 99%
“…Die Hüftgelenk sbeweglich keit wird präund postoper ativ als Gesamtfunkti onsmaß (G F) de r einzelnen Bewegungsmöglichkeiten des Gelen kes dokumen tiert (Reis et al. 1992).…”
Section: Zusamme Nfass Ungunclassified
“…Die Ergebnisse dieser Stud ie könn en mit einer Kon troll gruppe aus der Ort hop ädischen Universitätsklinik T übingen verglichen werde n, bei der ebenfalls eine individ uelle zeme ntfreie Prothese des selben Typs implant iert wurde und keine Ossifikationsprophylaxe durchgeführt word en ist (R eis et al, 1992). Reis et al (1992) finde n bei 55,1% dieser Patien ten periartikuläre Ossifika tionen , wobei 16,0% Verknöc heru ngen nach Stad ium Arcq 11 und 1,4% Verknöcher ungen nach Stadium A rcq III aufweisen. Die mit ein er fraktionierten Bestra hlung prophylaktisch behandelten Patienten zeigen demgege nüber in 10,3% der Fälle Verknöcherungen.…”
Section: Diskussionunclassified
“…RT can be given either postoperatively within 3 days of surgical treatment or preoperatively a few hours before surgery with varying results reported [1,8,14]. Moreover, NSAIDs, especially indomethacin, have been extensively used for the prevention of HO in various daily doses and durations of therapy [7,18,19]. However, despite the widespread use of both therapies, the type of therapy, the dose, and the duration of treatment have not yet been well established.…”
Section: Introductionmentioning
confidence: 99%